2020
DOI: 10.7554/elife.56760
|View full text |Cite
|
Sign up to set email alerts
|

Vessel noise levels drive behavioural responses of humpback whales with implications for whale-watching

Abstract: Disturbance from whale-watching can cause significant behavioural changes with fitness consequences for targeted whale populations. However, the sensory stimuli triggering these responses are unknown, preventing effective mitigation. Here, we test the hypothesis that vessel noise level is a driver of disturbance, using humpback whales (Megaptera novaeangliae) as a model species. We conducted controlled exposure experiments (n = 42) on resting mother-calf pairs on a resting ground off Australia, by simulating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 39 publications
0
40
0
1
Order By: Relevance
“…We ran a backwards PCoD model to determine if a "worst case" exposure regime would lead to population-level consequences via increased calf mortality. Here, we assumed the repercussion of the seismic survey was the reduced opportunity for nursing, given a decrease in resting behavior (and likely nursing) has been found in humpback whales in the presence of vessels (Morete et al, 2007;Sprogis et al, 2020). The maximal amount of milk a calf can receive is limited by the rate of delivery from the mother and the time available for feeding.…”
Section: Discussionmentioning
confidence: 99%
“…We ran a backwards PCoD model to determine if a "worst case" exposure regime would lead to population-level consequences via increased calf mortality. Here, we assumed the repercussion of the seismic survey was the reduced opportunity for nursing, given a decrease in resting behavior (and likely nursing) has been found in humpback whales in the presence of vessels (Morete et al, 2007;Sprogis et al, 2020). The maximal amount of milk a calf can receive is limited by the rate of delivery from the mother and the time available for feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, considering that the noise of the boats generated by the propeller cavitation produces adverse reactions in whale behavior (Erbe et al, 2019), and that more noise is produced at higher speed (Walker et al, 2019), the behavioral change of the animals may be due to the increase in the boats speed. Although we did not use the speed and path direction of the boats moving away as predictive variables, there is evidence that these variables negatively impact the behavior of large cetaceans (Heckel et al, 2001;Argüelles et al, 2016;Fiori et al, 2019), since this avoidance strategy increases the energetic cost for the animals (Williams et al, 2009;Sprogis et al, 2020b). We recommend that future studies incorporate other variables to describe the boat behavior, such as speed and direction of arriving and departing boats, to identify other potentially relevant factors in the responses of fin whales to WW.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is currently a strong concern over whether WW is an activity that really promotes the conservation of the subject species (Forestell, 2007). It has been widely reported in the literature that inadequate management of WW is an important source of perturbation for the animals, both in the short-and long-term (e.g., Corkeron, 2004;Bejder et al, 2006a;Argüelles et al, 2016;Sprogis et al, 2020b). Important sources of perturbation include a high number of boats in a confined area, very close proximity to the animals, the time and manner of approaching (and leaving) the animals, and lack of regulations or non-compliance with existing norms and regulations (Hoyt and Parsons, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, behavioral changes can occur before boats enter this threshold distance (e.g., Watkins, 1986;Baker and Herman, 1989;Sprogis et al, 2020a). Sprogis et al (2020b) demonstrated that vessel noise drives the behavioral response of humpback whales to boats. Although, we recorded the number of boats and their timing with the whales, the limitations imposed by the distance of the land-based survey, precluded us to unravel the role of noise of the boats on the behavior of the whales.…”
Section: Sampling Methodsmentioning
confidence: 99%